2016
DOI: 10.1016/j.mmcr.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Fungemia due to Kodamaea ohmeri in a young infant and review of the literature

Abstract: Fungal infections have become an important cause of morbidity and mortality in hospitalized children due to many complicating and underlying conditions. We present the case of a newborn infant with fungemia due to Kodamaea ohmeri who had a good outcome of the infection after using the combination of antifungal treatment and central venous catheter removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Similarly, MIC 50 values and MIC ranges generated from data collected during an exhaustive 12-year surveillance program in France (8) were very similar to those reported for the same species in the current report (Table 5). Moreover, a number of anecdotal case reports support our evidence for elevated MICs or fluconazole resistance in many of the species listed in Table 2, including Yarrowia (Candida) lipolytica (7,8), Pichia cactophila and Pichia norvegensis (7,8,(26)(27)(28)(29), C. blankii (30), Candida palmioleophila (7,31), Candida zeylanoides (29,32,33), Diutina (Candida) catenulata (7,34), Pichia fermentans (29), Pichia mandshurica (8), Debaryomyces hansenii (Candida famata) (29,35,36), Kodamaea ohmeri (8,35,(37)(38)(39), Trichosporon spp. (39)(40)(41), Rhodotorula spp.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, MIC 50 values and MIC ranges generated from data collected during an exhaustive 12-year surveillance program in France (8) were very similar to those reported for the same species in the current report (Table 5). Moreover, a number of anecdotal case reports support our evidence for elevated MICs or fluconazole resistance in many of the species listed in Table 2, including Yarrowia (Candida) lipolytica (7,8), Pichia cactophila and Pichia norvegensis (7,8,(26)(27)(28)(29), C. blankii (30), Candida palmioleophila (7,31), Candida zeylanoides (29,32,33), Diutina (Candida) catenulata (7,34), Pichia fermentans (29), Pichia mandshurica (8), Debaryomyces hansenii (Candida famata) (29,35,36), Kodamaea ohmeri (8,35,(37)(38)(39), Trichosporon spp. (39)(40)(41), Rhodotorula spp.…”
Section: Discussionsupporting
confidence: 70%
“…No additional studies were found during the hand‐screening of the included articles' references. Finally, 35 met the present study's inclusion criteria 3,4,7–39 . The review process is graphically presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 35 studies on K ohmeri infections, 30 (85.7%) reported fungemias, accounting for 36 patients out of 44 (81.8%) in total 3,4,7–34 . A concomitant infection was present in 22.2% (8 out of 36 fungemias), namely infective endocarditis (IE) in 11.1% (4 cases), 31–34 skin and soft tissue infection (SSTI) in 5.6% (2 cases), 16,21 disseminated infection with involvement of the spleen, urinary tract and lower respiratory tract in 2.8% (1 case), 8 and lower respiratory tract infection in 2.8% (1 case) 29 .…”
Section: Resultsmentioning
confidence: 99%
“…There have been 88 reports of infection with K. ohmeri described in the literature. Among them, 76 patients presented with fungaemia and the remaining presented with peritonitis (three patients), endocarditis (four patients), urinary tract infection (one patient), polymicrobial wound infection (one patient) and oral ulcer (three patients). In the present case, the lesion was exclusively limited to the site of the wound without systemic involvement.…”
Section: Discussionmentioning
confidence: 99%